Performance of Public Listed banks in ASEAN - Chin, Amy Ee Ling (Universiti Malaysia Sarawak (UNIMAS), 2013)
rhe study is conducted to measure the performance of public listed banks in the five ASEAN countries namely, Malaysia, Singapore, Indonesia, Thailand and the Philippines. This study covers e a total of 63 public listed banks which include 10 banks from Malaysia, 3 banks from Singapore, 28 banks from Indonesia, 10 banks from Thailand, and 12 banks from the Philippines. By employing CAMEL analysis, this study measures the banking performance over the period of 1997 to 2011. The CAMEL analysis methodology is based on five indicators which are Capital Adequacy, Asset Quality, Management Efficiency, Earning Quality and Liquidit~. The objectives of the study are to measure the performance of public listed banks as well as to investigate the impact of financial crisis on their performance. The results of the CAMEL analysis show that Singaporean public listed banks are the top performer as compares to their counterparts. Based on the five indicators of CAMEL, Thailand' s public listed banks have the best performance in capital adequacy, Malaysia's public listed banks has the best performance in asset quality, Singapore's public listed banks has the best performance in management efficiency, while the Philippines' public listed banks has the best performance in both earning quality and liquidity. Next, the comprehensive results reveal that Public Bank in Malaysia, United Overseas Bank in Singapore, Bank Artha Graha in Indonesia, Bank of Ayudhya in Thailand and Union Bank of the Philippines in the Philippines are the banks with best performance by country. Moreover, the results of this study discover that the impact of global financial crisis in 2008 on ASEAN banking lS relatively less severe as compares to the Asian financial crisis in 1997.